2008
DOI: 10.1093/pasj/60.sp1.s11
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Non-X-Ray Background for the X-Ray Imaging Spectrometer aboard Suzaku

Abstract: One of the advantages of the X-ray Imaging Spectrometer (XIS) system on board Suzaku is its low and stable non-X-ray background (NXB). In order to make the best use of this advantage, modeling the NXB spectra with high accuracy is important to subtract them from the spectra of on-source observations. We construct an NXB database by collecting XIS events when the dark Earth covers the XIS FOV. The total exposure time of the NXB data is about 785 ks for each XIS. It is found that the count rate of the NXB anti-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(142 citation statements)
references
References 17 publications
3
138
1
Order By: Relevance
“…We start with the particle background. The reproducibility of this background component for Suzaku is better than about 3% (e.g., Tawa et al 2008). Here, we conservatively assumed 5% and found best fit temperatures and errors for the third bin as 4.66 +0.81 −0.65 keV and 4.32 +0.77 −0.54 keV.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We start with the particle background. The reproducibility of this background component for Suzaku is better than about 3% (e.g., Tawa et al 2008). Here, we conservatively assumed 5% and found best fit temperatures and errors for the third bin as 4.66 +0.81 −0.65 keV and 4.32 +0.77 −0.54 keV.…”
Section: Discussionmentioning
confidence: 86%
“…For Chandra and XMM-Newton, temperature measurements in the low surface brightness cluster outskirts are strongly affected by the uncertainty in the particle background. We tested the influence of the particle background on the Suzaku results by artificially changing the normalization of the Night Earth spectra by a very conservative (e.g., Tawa et al 2008) ±10% and repeating the fitting procedure. We found that the new best fit temperatures are consistent with the statistical uncertainty of the standard fit (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also discarded pixels adjacent to the flickering pixels. Non X-ray backgrounds (NXBs) were estimated by xisnxbgen (Tawa et al 2008). Redistribution matrix files and ancillary response files were produced by xisrmfgen and xissimarfgen (Ishisaki et al 2007) We then fitted the relation between the true energies and the centroid energies of the Gaussians with a first-order polynomial.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…The region representing the whole remnant has a size of 4 .85 The background for 3C 391 is a combination of the non-X-ray background (NXB), the cosmic X-ray background (CXB) emission, and the Galactic ridge X-ray emission, GRXE (Koyama et al 1986). First, we estimated the NXB data from night Earth observations using the tool xisnxbgen (Tawa et al 2008), and subtracted the NXB from the spectrum. We selected the background region, the nearby blank sky region (Obs.ID 500009020) on the Galactic plane, consisting of the GRXE and the CXB.…”
Section: Background Estimation and Model Fittingmentioning
confidence: 99%